Formulation based predictive cure kinetics modelling of epoxy resins - Voto, Gabriele; Sequeira, Leela; Skordos, Alexandros A. (Elsevier, 2021)
Matrix formulation for aero-grade high-performance carbon fibre reinforced thermoset composites is a challenging task relying on extensive knowledge of chemistry, legacy information and trial-and-error iterations to identify a suitable pre-polymer resin/curative combination. This work proposes the development and application of a cure kinetics methodology to tailor preliminary matrix formulations focusing on matrix constituents reactivity. The kinetics of a ternary system containing either one epoxy pre-polymer and two amine curatives or two epoxy pre-polymers and one amine curative is approximated as a linear combination of the kinetics of its elementary binary systems containing the corresponding epoxy pre-polymer and amine curative. The method has been evaluated on a wide range of epoxy/amine formulations and shown to be valid with a reaction rate error lower than 0.003 min−1. The application of this predictive method allows the design of matrix systems with tailored reactivity and cure time without extensive experimentation.
Keywords: composite matrices; matrix composition design; formulation ratio superposition; thermosetting resin; amine curative; cure kinetics; process modelling; composites manufacturing